Do this in remembrance of me : the disputed works in the Lukan Institution narrative (Luke 22: 19b-20) : an historico-exegetical, theological, and sociological analysis - Billings, Bradly S. (Library of New Testament studies, 2006)
This title posits a new explanation of the longstanding textual problem affecting the Words of Institution in St. Luke's Gospel, by arguing that the social situation of the early Christian community explains why such emendations were made. €€€. By examining the manner in which manuscripts function as windows into the social world of early Christianity, Billings provides a fruitful study of the longstanding gap in our knowledge of a significant textual problem represented by the Western Text of Luke.